Contracting institutions and firm boundaries - Peter S. Eppinger; Bohdan Kukharskyy (University of Tübingen, Faculty of Economics and Social Sciences, 2017)
Contractual frictions are widely known to shape firm boundaries. But do better contracting institutions, which reduce these frictions, induce firms to be more or less deeply integrated? This paper provides a large-scale investigation of this question using a unique micro dataset of ownership shares across half a million firm pairs worldwide. We uncover strong evidence that better contracting institutions in subsidiaries' countries favor deeper integration, particularly in relationship-specific industries. We formally show that these findings can be explained by a generalized Property-Rights Theory of the firm featuring partial ownership, while they are at odds with the canonical Transaction-Cost Theory.
urn:nbn:de:bsz:21-dspace-777964
Keywords: F21; F23; D02; D23; L14; L23; 330; firm boundaries; contracting institutions; multinational firms; property-rights theory; firmlevel analysis